2007
DOI: 10.1007/s00467-006-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Distal RTA with nerve deafness: clinical spectrum and mutational analysis in five children

Abstract: Distal renal tubular acidosis (RTA) with nerve deafness is caused by mutations in the ATP6V1B1 gene causing defective function of the H+ -ATPase proton pump. We report five acidotic children (four males) from four unrelated families: blood pH 7.21-7.33, serum bicarbonate 10.8-14.7 mEq/l, minimum urinary pH 6.5-7.1 and fractional excretion of bicarbonate in the presence of normal bicarbonatemia 1.1-5.7%. Growth retardation and nephrocalcinosis, but not hypercalciuria, were common presenting manifestations. Hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…In fact, normocalciuria is not uncommon at diagnosis in young dRTA patients (51 year). 4,14,15 As we all know, many factors can contribute to the differences in urinary calcium excretion, such as dietary, calcium absorption and hormonal control, as well as renal handling of calcium. Three (patient I-1, II-1 and IV-1) of the four patients with normocalciuria had evident signs of dehydration resulted by vomiting, fever, or other causes at diagnosis in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, normocalciuria is not uncommon at diagnosis in young dRTA patients (51 year). 4,14,15 As we all know, many factors can contribute to the differences in urinary calcium excretion, such as dietary, calcium absorption and hormonal control, as well as renal handling of calcium. Three (patient I-1, II-1 and IV-1) of the four patients with normocalciuria had evident signs of dehydration resulted by vomiting, fever, or other causes at diagnosis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The coding region and adjacent intronic segments of the ATP6V1B1 and SLC4A1 genes were amplified using of previously described primer pairs, respectively. 2,14 PCRs were performed in 50 lL of solution containing 0.2 mM dNTP, 0.03 U/lL Taq polymerase (Takara EX Taq Hot start version, DRR006B, Osaka, Japan), 2.0 mM MgCl 2 , 2.5 lL 10 Â PCR Mg 2+ -free buffer (Takara), approximately 50 ng genomic DNA and 1 mM of each primer. PCR was performed with an initial denaturation step at 95 C for 5 min, subsequently followed by 33 cycles with denaturation at 95 C for 45 s, annealing at 52-66 C for 45 s and elongation at 72 C for 45 s. PCR samples were subjected to bidirectional sequencing.…”
Section: Mutation Analysismentioning
confidence: 99%
“…Patient’s genetic data and previously published mutations [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30] are presented in table 2. A mutation in CAII (c.583G>C, patient 4) that had never been reported before was found among them.…”
Section: Resultsmentioning
confidence: 99%
“…One possible mechanism may be related to their increased tendency to develop nephrocalcinosis complicated by renal stone disease [32]. We and others [21] clearly demonstrated that this group is prone to nephrocalcinosis compared to the CAII group. Nephrocalcinosis can impair tubular function by mechanical blockage of tubular fluid flow, followed by tubular atrophy, interstitial inflammation and interstitial fibrosis, and lead to the development of chronic kidney disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the genetic and molecular basis, as well as the clinical, biochemical, and radiological findings useful to identify the subtype of RTA [1][2][3][4][5][6][7][8][9][10][11][12]. Information on acquired forms of RTA secondary to drugs and toxins or associated to systemic diseases is not included because this review mostly deals with congenital primary types of RTA, which are more frequently found in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%